FAKTOR-FAKTOR YANG MEMPERNGARUHI INDEKS PEMBANGUNAN MANUSIA: ANALISIS DATA PANEL DI ASEAN-5 - oktadian DIAN sari; Winda Fuji Lestari (P3M STIE Mulia Darma Pratama, 2026)
A country's progress is not only measured by per capita income, but is also reflected in the Human Development Index (HDI). The Human Development Index assesses development achievements that include education, health and decent living standards. This study aims to examine the influence of electricity consumption, FDI and economic growth on the Human Development Index in five ASEAN member countries, namely Indonesia, Malaysia, Singapore, Thailand and the Philippines with a research time span of 2010-2023. Using the Fixed Effect Model (FEM) estimation method, it shows that the higher economic growth, the higher the HDI of a country. Meanwhile, FDI contributes positively and significantly to the increase in the Human Development Index. The amount of foreign direct investment received will encourage the improvement of human quality. In this study, it was also found that the variable of electricity consumption has a positive and significant influence on the Human Development Index. These findings confirm that increased economic growth, foreign direct investment (FDI) and electricity consumption are strategic factors in encouraging the improvement of HDI quality in ASEAN member countries.